PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN I BASA AMPEK BALAI - Fitri, Sesna; Rahmi, Rahmi; Aima, Zulfitri (Pendidikan Matematika, 2013)
The research was due to the lack of studentâ interest, motivation and activities during teaching and learning process. Students tent to be more individual. The teaching process was teacher-centered. The studentsâ understanding of mathematic concept was low. It was seen from their mathematic result. That was grade VIII students of SMPN I Basa Ampek Balai 2012/2013 year of entrance. The research aimed at understanding how far the students of grade VIII SMPN I Basa Ampek Balai understood the mathematic concep using active learning the Power of Two technique with a quiz, whether it was better than the convensional one. The design was experimental research using random sampling technique. The populasion was students of grade VIII SMPN I Basa Ampek Balai. Based on the result of random sampling tekhnique, grade VIII.4 was chosen as the experimental group, while the grade VIII.6 as the control group. The instrument used was a quiz and essay mathematic test. The reliability of the test was 0.825. BasedÂ  the data analysis, it was obtained tyhat both class were homogeny and normal. The technique analysis data used was one way to test. Based on the analysis of hypothesis using MINITAB, it was obtained that the p-value=0.002 was < Î±=0.05. Therefore, it can be concluded thad studentsâ math concept understanding using active learning The Power of Two with a quiz was better tahn that of conventional technique with the 95% degree of certainty.